Pengaruh Upah Minimum Kabupaten (UMK) Di Kabupaten Wonosobo Terhadap Kesejahteraan Pekerja - Eva Shifdlotul Gisna; Carlos Damero; Nabila Mauldy Erwanto; Muhammad Naufal Nabiila (Pusat Riset dan Inovasi Nasional, 2024)
Wages are often one of the issues that is always in the spotlight. This is because many companies and entrepreneurs have complied with the Regency Minimum Wage (UMK) or even above the UMK standard, showing their commitment to worker welfare. However, in fact there are still a number of companies that have not fulfilled this obligation and pay wages below the UMK standard. This creates disparities in the protection of workers' rights and highlights the need for tighter supervision and stricter law enforcement to ensure all companies comply with applicable labor regulations. This research aims to analyze the influence of the Regency Minimum Wage (UMK) in Wonosobo Regency on Workers' Welfare. This research discusses the importance of MSE policy in improving community welfare. The implication of the proposed policy is the need for continuous adjustment of the MSE in accordance with the level of inflation and economic growth, as well as expanding efforts to increase productivity and workforce skills to support the overall welfare of society in Wonosobo Regency.